AVALIAÇÃO FARMACOECONÔMICA DE USUÁRIOS DE VARFARINA - RAQUEL UHDICH KLEIBERT , KARINE; FIN HERMANN , EMELLI; LORENZONI NUNES , PAULA; VINICIUS DAHMER ALVES , MARCOS; SCHNEIDER , ALINE; DE FATIMA COLET , CHRISTIANE (Salão do Conhecimento, 2020)
Trabalho vinculado ao Projeto de mestrado: